EVALUASI PENERAPAN KULTUR TEKNIS PADATANAMAN KELAPA SAWIT MENGHASILKAN DI PERKEBUNAN KELAPA SAWIT DI KABUPATEN BERAU KALIMANTAN TIMUR - Dwi Suryani; Rusli Anwar; Rusmini; Fadli Mulyadi; Sri Ngapiyatun (JURNAL AGRIMENT, 2019)
Background of this study is on how the right plantation management practices become the absolute provision to gain eminent yield. Thus the company must evaluates the application on the technical culture of mature plant in order to know how big is the value and influence of the technical culture application so that the company can attain the optimum production.Therefore this study aims to identify and calculate the application rate of cultivation technique factors that have been applied by the company itself also to calculate the loss rate from misapplication of cultivation techniques that have been affected oil palm production based on the cultivation technical manual and estimated loss value incurred by PPKS Medan and identify the efforts made by the company to control pests and diseases (HPT) also the development of oil palm pollinating insects (SPKS). The method used in this study was field observation method, and descriptive statistical analysis (tabulation). There were some indicators that used in field observation in this study, they are imperfect pollination in fruit development phase, oil extraction rendement (OER) and kernel extraction rendement (KER), harvesting technique and discipline on collecting loose fruits, harvesting unripe fruits, harvesting rotation >15 days, crop damage due to rat pests. The result showed that the technical culture application rate has different value in each indicator, based on the highest error rate the first was harvesting rotation > 15 days (52,75 %), second was imperfect pollination (7,05 %), third was harvesting technique and discipline on collecting loose fruits (7%), forth was crop damage due to rat pests (4,3%) and the last was harvesting unripe fruit (3,4%). The different value in application rate could be influenced by inadequate human resources, lack in controlling, facilities and infrastructure availability (like pollinating insect box, harvesting tools and good transportation access)